Tracking the Performance of the Malawi Agricultural Sector: 2010/11 to 2011/12 - By Malawi’s Agricultural Sector Wide Approach Technical Working Group On Monitoring And Evaluation (ASWAP TWG On M&E) (International Food Policy Research Institute, 2013)
In June 2012, a Technical Working Group on Monitoring and Evaluation (TWG on M&E) was established in Malawi to track agricultural sector performance under the overarching sector strategy, the Agricultural Sector Wide Approach (ASWAp). The TWG on M&E brings together a wide variety of stakeholders representing the public sector, non-state actors, and development partners. Each stakeholder provides updates on key indicators considered critical for evalu-ating the performance of Malawi’s agriculture sector. The International Food Policy Research Institute (IFPRI), under the auspices of the Malawi Strategy Support Program (MaSSP), provides technical support to the TWG on M&E. Over the period September 2011 to September 2012, an analysis of the consolidated indicator set reveals that some aspects of the agriculture sector improved greatly, while others have either stagnated or declined.